2022
DOI: 10.1177/09603271221084671
|View full text |Cite
|
Sign up to set email alerts
|

Association of miR-9-5p and NFIC in the progression of gastric cancer

Abstract: Background Gastric cancer is the most common malignant neoplasm of digestive system. Herein, we aim to detect the expression of nuclear factor I C (NFIC) in gastric cancer cells, and to explore the effect and mechanism of its expression on the development of gastric cancer. Methods qPCR and Western blot assays were carried out to detect NFIC expression. Then, BGC-823 and SGC-7901 cell lines were selected to perform the following functional experiments. The function of NFIC on gastric cancer cells was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is important to mention that the TF NFIC targets nine cuproptosis regulators in the regulatory network, implying that NFIC may be a key upstream TF of cuproptosis. The role of NFIC in the regulation of growth and metastasis of a variety of tumors has been confirmed, and its mechanism involves the EMT process and nuclear factor kappa B pathway [ 62 , 63 , 64 , 65 , 66 , 67 ]. However, the association of NFIC with cuproptosis activity has never been characterized; therefore, we hypothesized that NFIC could also affect tumor development by regulating cuproptosis activity, which deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that the TF NFIC targets nine cuproptosis regulators in the regulatory network, implying that NFIC may be a key upstream TF of cuproptosis. The role of NFIC in the regulation of growth and metastasis of a variety of tumors has been confirmed, and its mechanism involves the EMT process and nuclear factor kappa B pathway [ 62 , 63 , 64 , 65 , 66 , 67 ]. However, the association of NFIC with cuproptosis activity has never been characterized; therefore, we hypothesized that NFIC could also affect tumor development by regulating cuproptosis activity, which deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Our recent research demonstrated that miR-9 can augment the tumor-initiating potential of breast cancer cells through a transgenic mouse model. 17 Nevertheless, in the context of lung, 18 gastric, 19 and pancreatic 20 cancers, miR-9 might function as a tumor suppressor. Nonetheless, the intricate mechanisms through which miR-9 modulates the immune microenvironment in breast cancer remain incompletely elucidated.…”
Section: Introductionmentioning
confidence: 99%